ECONOMIC AND FINANCIAL FEASIBILITY OF IMPLEMENTING A MEAD-PRODUCING MICROINDUSTRY - Suzart Araújo, Geiza; de Souza, Sílvia Maria Almeida; de Carvalho , Giovani Brandão Mafra; Martínez, Ernesto Acosta (Revista Interface Tecnológica, 2021)
The present study aimed to carry out the economic feasibility study of a microindustry producing mead supplemented with siriguela pulp and soybean bran extract, installed in the municipality of Ribeira do Pombal, BA. For the development of the study, researches were carried out, bibliographic and experimental, obtaining important data for the elaboration of the cash flow: fixed and variable costs, investment, depreciation, fees, taxable profit, income tax, net flow, amortization and performance bonus. The investment valuation methods [net present value (NPV), internal rate of return (IRR) and the payback method] were also applied. The investment of the project for monthly production of 2250 L of mead was R 305,419.84, resulting in the following economic indicators: NPV (R 5,861.03), IRR (23%), simple payback (2 years) and discounted payback (3 years), considering the minimum attractiveness rate of 15% and a useful life of 10 years. Therefore, the project was considered economically viable, in addition to being a possibility for income generation for family farmers.